Chemical Constituents, Proximate Composition and Hepatoprotective Activity of Abutilon muticum - Shahid, S.; Kashmiri, M.A.; Adnan, A.; Ali, B. (Asian Journal of Chemistry, 2011)
Phytochemical studies of the aerial parts of Abutilon muticum resulted in the isolation of eight new source compounds, which had not been isolated so far from this investigated source. The compounds isolated were: 3,4',5,6,7-pentahydroxy flavones; 3,3',4',5,7-penta hydroxy flavone- 8-O-b-D-glucopyranoside, 3,3',4',5,7-pentahydroxy flavones; stigmasterol, benzoic acid, 1- tricosanol, cholesterol and triacontyl palmitate. Proximate composition of A. muticum revealed that the protein content was appreciable (23.5 %) and similar to that of cotton (28.72 %). As far as human nutritional aspects are concerned A. muticum had significant mineral contents. Potassium is most abundant (443.01 mg/100 g), followed by calcium (395.23 mg/100 g), phosphorus (327.13 mg/100 g) and magnesium (193.42 mg/100 g). In addition hepatoprotective activity of A. muticum was evaluated against hepatic damage in rabbits. The substantially elevated enzyme levels were restored towards normalization significantly by the extracts. The biochemical observations were supplemented with histopathological examination of rabbit liver sections. These findings reveal A. muticum, indigenous to Pakistan to be potentially valuable herb for minerals, delivery of drugs and liver diseases.